A companion to the anthropology of the Middle East - Altorki, Soraya; Ohio Library and Information Network (Hoboken, NJ : Wiley-Blackwell, 2015)
"A Companion to the Anthropology of the Middle East presents a comprehensive overview of current trends and future directions in anthropological research and activism in the modern Middle East"--
Includes index
Includes bibliographical references and index at the end of each chapters
Keywords: Ethnology -- Middle East; Middle East -- Social life and customs; Electronic books; Electronic book